Landscapes, images, writings (Simbiótica. Revista Eletrônica, 2022)
In recent academic debate, the theme of landscape has raised meaningful questions, calling attention for a dialogue among Human Sciences, Literature and Arts. This dossier is an invitation to think about compositions among landscapes, images and writings in their approximations, crossings, remission, trails or even losses. If it is possible, we explore some inquiries: Which images and writings a landscape can claim? How much (or what) of writing is extended in a landscape? What matter of the landscapes are the images made of? Or, yet, of what images do the landscapes embody themselves? As we have glimpsed, the landscape can evoke path, it refers as much to earth as it elevates us to other atmospheres: the thought and the imagination. Landscapes are ways of existing, constitute themselves as gaze, reminiscence, and memory; allude, yet, to the plasticity of art and to the drawing of the writing, they adorn each other in the materiality of the inks as well as in the stain, they sprout in the poetical forms and in the narrative experiences. To this dossier, we are interested in proposals that face these (and other) expressions of landscape in their manifestations; we included here some possible paths to be taken: writing plasticity; images and words; narratives of the landscapes; images of thought; landscape poetics; dwell landscapes; walk-write-landscapes; landscape and memory.